Implementation of technological controls for Continuous Improvement in reducing accidents in shaft construction - Berrocal Argumedo, Kelvis (2021)
The general objective of this study is to determine the effect of the implementation of technological controls for Continuous Improvement in reducing accidents in shaft construction - Geminis Mining Corporation, Peru. The study is based on the statistical analysis of accident rates and control measures: geotechnical, administrative and security itself, as well as responsible, committed and appropriate participation in the development and optimization of security through control, mainly technological, to reduce accidents, as has been proven from 2010 to 2017. The study variables are defined and exhaustively analyzed to determine the relationship that exists from a mainly quantitative perspective that allows a better appreciation of the effects. Finally, conclusions are considered that express the intention of the investigation, and some suggestions are proposed for the better control of security.